When Is a Barrier Island Not an Island? When It Is Preserved in the Rock Record - Mulhern, Julia S.; Johnson, Cari L.; Green, Andrew N. (Frontiers in Earth Science, 2021)
Existing barrier island facies models are largely based on modern observations. This approach highlights the heterogeneous and dynamic nature of barrier island systems, but it overlooks processes tied to geologic time scales, such as multi-directional motion, erosion, and reworking, and their expressions as preserved strata. Accordingly, this study uses characteristic outcrop expressions from paralic strata of the Upper Cretaceous Straight Cliffs Formation in southern Utah to update models for barrier island motion and preservation to include geologic time-scale processes. Results indicate that the key distinguishing facies and architectural elements of preserved barrier island systems have very little to do with ‘island’ morphology as observed in modern systems. Four facies associations (FA) are used to describe and characterize these barrier island architectural elements. Barrier islands occur in association with backbarrier fill (FA1) and internally contain lower and upper shoreface (FA2), proximal upper shoreface (FA3), and tidal channel facies (FA4). Three main architectural elements (barrier island shorefaces, shoreface-dominated inlet fill, and channel-dominated inlet fill) occur independently or in combination to create stacked barrier island deposits. Barrier island shorefaces record progradation, while shoreface-dominated inlet fill records lateral migration, and channel-dominated inlet fill records aggradation within the tidal inlet. Barrier islands are bound by lagoons or estuaries and are distinguished from other shoreface deposits by their internal facies and outcrop geometry, association with backbarrier facies, and position within transgressive successions. Tidal processes, in particular, tidal inlet migration and reworking of the upper shoreface, also distinguish barrier island successions. In sum, this study expands barrier island facies models and provides new recognition criteria to account for the complex geometries of time-transgressive, preserved barrier island deposits.